Du vécu subjectif aux savoir-faire professionnels des professeurs d'école débutants - Magali Boutrais (Nantes Université, 2015)
When the Department of Education uses a reference table of skills to form primary school teachers, we shall see how this "professionalization" of teacher's job in primary school takes shape. We suggest studying the novice primary school teachers experience subjective as being a dimension of the construction of its professionalism. To encircle this " subjective construction of the individual experience ", we led elucidation interviews (Vermersch,1994) with several primary school teachers in the first one or in the second year of exercise, within the framework of our doctorate. The analysis of an extract of interview concerning real-life moments of class allows us to identify actions in situation. These shares result at the same time from the implementation of knowledges and grips of furtive information, in an instant, followed by immediate decision-making on behalf of the primary school teacher. This construction of professional know-how participates in the construction of the professional identity. To encircle this process, we choose to observe the verbalizations obtained according to a plan articulating grips of information, identification, decision-making. As the object of a current doctoral thesis, we shall deliver, in this article, an example of the first results stemming from the analysis of an interview.